The burden and underlying determinants of under nutrition among under five year children in Gurage Zone - Egata, Andamlak Dendir; Nida, Abdusemd Worku (Asian Journal of Medical Sciences, 2019)
Background: Malnutrition is one of the most common causes of morbidity and mortality in children under the age of five year. However, in Gurage zone information about the prevalence and associated factors of malnutrition still limited. Aims and Objectives: The major objective of this study was assessing the burden and determinants of malnutrition among under five children. Materials and Methods: A community based cross-sectional study design was applied from December 25, 2016 to April 25, 2017. A total of 1040 eligible mothers were interviewed using structured interviewer administered questionnaires by trained data collectors working in pediatrics ward. Through systematic sampling technique study participant were included in the study. To test the existence of statistical relationship between independent and dependent variables multiple logistic regressions analysis was used. Results: The prevalence of malnutrition among study children was 38.8%. Logistic regressions analysis result indicated that Unimproved sanitation [AOR 1.58 (95% CI 1.13-2.2)], food insecurity [AOR 2.06 (CI 3.49-3.33)], maternal disempowerment [AOR 4.1(CI 2.69-6.24)], inadequate frequency of exclusive breast feeding [AOR 1.9 (95% CI 1.176-3.357]. showed a significant association with malnutrition. Conclusion: The prevalence of malnutrition among under five year children living in Gurage zone was 38.8%. It was associated with utilization of unimproved sanitation, maternal disempowerment, food insecurity. Hence to abort the problem, it is better to enhance house hold food security, exclusive breast feeding, maternal empowerment and utilization of improved sanitation.